An Epistemology of Play: Provocation, Pleasure, Participation and Performance in Ethnographic Fieldwork and Film-making - Sjöberg, Johannes (Anthropologica, 2018)
Drawing on previous and ongoing research on ethnofiction films, this article suggests new perspectives on ethnographic fieldwork and film-making, where play stands at the centre of the epistemology. Projective improvisation in ethnofiction shares common denominators with play and especially role play, in which provocation, pleasure and flow motivate the performance. The article presents co-creative role play as a valid ethnographic method, based on the assumption that mimicry gives access to the implicit information of the play world, making it explicit through a reflexive approach.